A model for a shariah-compliant cryptocurrency adoption - Saleh, Al-Hussaini Abulfathi Ibrahim (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
Cryptocurrency is a peer-to-peer digital exchange system that generates and distributes tokens using cryptography. Concerning the Islamic view of cryptocurrency, Shari'ah scholars and financial experts have formed varying views, with some finding it permissible (halal) and others prohibiting it (haram). As a result, the aim of this study is to examine the factors of implementing cryptocurrency from an Islamic perspective, to assess the mediating factors of implementing cryptocurrency from a Muslim perspective, and to propose a model of implementing cryptocurrency from a Muslim perspective. Given the lack of an Islamic digital currency model and the importance of applying Islamic law, the study employs the Theory of Reason Action (TRA), the Technology Acceptance Model (TAM), Deindividuation theory, and the Shari'ah compliance e-commerce trust model, as well as a mixed-method research methodology that incorporates both qualitative and quantitative approaches. In this study, the unit of analysis is the individual level, as it is a stakeholder in cryptocurrency and its Islamic perception. In the quantitative research round, 307 people completed a significant number of items on the research questionnaire through web-based and face-to-face methods. For qualitative research, the sample size is nine informants. In both cases, the samples include individuals who are familiar with cryptocurrencies, especially Bitcoin and its Islamic perspective. The following results can be taken from the study of both qualitative and quantitative research: 1) "Emotionality" significantly influences "Behavioral Intention to Use Cryptocurrency (Bitcoin)" as well as mediating "Financial concern", "Shari'ah Compliance" towards Intention to Use Cryptocurrency (Bitcoin). This has been the study's main finding toward a new development of theory. 2) For the Qualitative findings, many experts in the field of Muslim cryptocurrency conclude that cryptocurrency is purely an accounting treatment that brings what is required of transparency and the accuracy of reporting, which is embedded in the hadith of (the) Prophet sallallahu 'alayhi wa sallam. Moreover, the results revealed that cryptocurrency can be accepted as a commodity or a piece of merchandise just like software. There is no objection to trading it as a commodity for someone who thinks that it will help him if there is a guarantee of not losing his money. The Hanafi and Maliki schools of thought agree that anything used in a financial transaction must be either a commodity, a currency, or a financial asset. it was uncovered that, if this Bitcoin transaction is measured according to the rules of Islamic law, it violates the Holy book of Allah, as well as the Sunnah of our prophet (SAW), unless anything else is established. These were some of the research's practical contributions, this study contributes to the debate over the legitimacy of cryptocurrency transactions from an Islamic perspective by specifying the requirements for considering cryptocurrencies as a legitimate or illegal digital transaction method. The findings would be beneficial for investors and Islamic finance experts.